Atrial fibrillation after cardiac surgery Prevention and management: The Australasian experience - Alawami, Mohammed (Journal of the Saudi Heart Association, 2018)
BACKGROUND: Atrial fibrillation (AF) after cardiac surgery is a major health problem that is associated with a significant financial burden. This paper aims to highlight this problem and review the current guidelines in the prevention and management of AF after cardiac surgery, providing our experience in the Australasian centers